2015
DOI: 10.1016/j.celrep.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Analysis of the Slx1-Slx4 Endonuclease

Abstract: SummaryThe SLX1-SLX4 endonuclease required for homologous recombination and DNA repair in eukaryotic cells cleaves a variety of branched DNA structures. The nuclease subunit SLX1 is activated by association with a scaffolding protein SLX4. At the present time, little is known about the structure of SLX1-SLX4 or its mechanism of action. Here, we report the structural insights into SLX1-SLX4 by detailing the crystal structure of Candida glabrata (Cg) Slx1 alone and in combination with the C-terminal region of Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 45 publications
4
70
0
Order By: Relevance
“…As a control, we generated an SMX mutant containing catalytic mutations in SLX1 (R41A and E82A), MUS81 (D307A), and XPF (D705A). These mutations impaired the activities of SMX (Figure S2E), as observed previously with the individual heterodimers (Enzlin and Schärer, 2002, Gaur et al., 2015, Wyatt et al., 2013). …”
Section: Resultssupporting
confidence: 87%
“…As a control, we generated an SMX mutant containing catalytic mutations in SLX1 (R41A and E82A), MUS81 (D307A), and XPF (D705A). These mutations impaired the activities of SMX (Figure S2E), as observed previously with the individual heterodimers (Enzlin and Schärer, 2002, Gaur et al., 2015, Wyatt et al., 2013). …”
Section: Resultssupporting
confidence: 87%
“…The interaction of Slx4 with Slx1 is mediated by Slx4’s HtH domain (Fig. 2) and a recent structural study in Candida glabrata showed that the interaction is responsible for dissociating an inactive Slx1 homodimer to promote its endonuclease activity (Gaur et al 2015). The importance of Slx1-Slx4, especially in the absence of Sgs1, is likely associated with the fact that replication forks stall with high frequency at the rDNA locus due to the presence of a polar replication fork barrier (RFB) (Brewer and Fangman 1988; Linskens and Huberman 1988).…”
Section: Slx4 As a Scaffold For Coordination Of Structure-specific Enmentioning
confidence: 98%
“…Each species can be derived from the four-way junction 3 (see Figure S4), and include a common strand (the x strand) that was radioactively [5'- 32 The GIG-YIG motif of human ANKLE1 is required for nuclease cleavage close to DNA branchpoints ANKLE1 has a highly conserved GIY-YIG domain at its C-terminal end ( Figure 4A). GIY-YIG domains function as the active centers of a number of nucleases (33), including R-Eco29kl (34), I-TevI (35), UvrC (36) and the junction-resolving enzyme SLX1 (37). For ANKLE1 the sequence is FTY 453 (31 amino acids) Y 486 VG.…”
Section: Ankle1 Cleaves Double-stranded Dna Close To Branchpointsmentioning
confidence: 99%